KINERJA PEGAWAI DITINJAU DARI KOMPETENSI SOSIAL, BUDAYA ORGANISASI, PENGALAMAN KERJA DAN DIVERSITAS MANAJEMEN SEBAGAI INTERVENING (Studi PT Bank Tabungan Negara Kantor Cabang Solo) - Muhammad Maulana Dwi Asmoro; Bambang Mursito; Istiatin Istiatin (JURNAL ILMIAH EDUNOMIKA, 2020)
Abstract : The purpose of this study was to determine social competence, organizational culture, work experience on employee performance through management diversity. This research method using quantitative quantitative descriptive method is data in the form of numbers. Sources of data in this study include primary data using questionnaires and secondary data from the source. The population of this study is primed by the sampling technique with the sampling technique in this study is convenience sampling. (2) Classic Assumption Test (Normality Test, Multicollinearity Test and Heteroscedasticity Test), (3) Hypothesis Test (Tiered Regression Analysis, T Test, F Test) and R2 test). The results of data analysis can be concluded: (1) Based on the test results can be obtained from the results of the incident that social competence, organizational culture, work experience on employee performance through management diversity. Keywords: Social Competence, Organizational Culture, Work Experience, Management Diversity and Employee Performance